Recent achievements of free‐standing material and interface optimization in high‐energy‐density flexible lithium batteries. Issue 3 (7th November 2022) - Zuo, Lanlan; Lu, Di; Yang, Tianyan; Yue, Dan; Li, Weidong; Ma, Qiang; Chen, Yufang; Zheng, Chunman; Wu, Xiongwei
Abstract: Lithium‐based batteries are the most potential state‐of‐the‐art energy storage device for flexible electronics. The flexible lithium batteries have the advantages of high energy density, robust mechanical durability, and stable power output even under dynamic deformation. Among them, the synergies of flexible free‐standing electrodes, solid electrolytes, and electrode–electrolyte interfaces are crucial to achieving the goal of high energy density and safety performance for flexible lithium batteries. Therefore, a thorough understanding of the interface formation mechanism and influencing factors is crucial for the design of flexible electrodes and solid electrolytes. In this review, the interface challenges in flexible lithium‐based batteries including interface formation, electrodes‐electrolyte interface, and interparticle interface characteristics are presented. Then, strategies of interface optimization are summarized and discussed. Following this, the interface of flexible lithium‐based batteries with novel architecture is introduced, including the interface between each component and unit of the battery. Finally, the perspectives for the future development of flexible lithium‐based batteries are also given. Abstract : The development of high energy density and stable power output of flexible lithium‐based batteries requires the cooperation of flexible components and advanced interfaces. However, interface issues seriously affect its stable power output under dynamic deformation. In this review, the formation and characteristics of the interface are elaborated in‐depth. The design of advanced flexible free‐standing materials, novel battery architecture, and the strategy of interface optimization are summarized, and rational opinions on eliminating the interface issues are also put forward.